PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN SUASANA TERHADAP KEPUTUSAN PEMBELIAN DI RICHEESE FACTORY AKSES UI DEPOK - Bonifasius M.H Nainggolan; Eko Budiman; Al Agus Kristiadi (LPPM Universitas Asa Indonesia, 2020)
The purpose of this study was to determine whether product quality, service quality and atmosphere influence purchasing decisions at Richeese Factory Access UI Depok. The analytical tool used to measure the effect of the elements mentioned above is multiple linear regression, and to analyze data using IBM SPSS Statistics 20. Based on this analysis, it can be concluded that simultaneously the variable product quality (X1), service quality (X2) , and the atmospheric variable (X3) affects purchasing decisions (Y). It was also concluded that partially (individually) product quality, service quality, and atmosphere influenced purchasing decisions. The results showed that product quality had the most significant effect on purchasing decisions at Richeese Factory Access UI Depok.